Tuesday

October 21, 2014

October 21, 2014

Posted by **M** on Wednesday, September 3, 2014 at 8:11pm.

6x^3+2x^2-8x =0

I know the GCF is 2x thus leaving:

2x(3X^2+X-4X)=0 *Stuck after this part*

- Math -
**Reiny**, Wednesday, September 3, 2014 at 8:19pmyour factored version is incorrect, the last term is wrong

2x(3x^2 + x - 4) = 0

which factors further to

2x(3x + 4(x - 1) = 0

so ..

x = 0 or x = -4/3 or x = 1

**Answer this Question**

**Related Questions**

math - Consider the following binomials. A=(x^2+5x) B=(6x+30) Part 1: Factor ...

math - Consider the following binomials. A=(x^2+5x) B=(6x+30) Part 1: Factor ...

math - Consider the following binomials. A=(x^2+5x) B=(6x+30) Part 1: Factor ...

GCF Math Check - Can you see if my answers are correct? Directions find the GCF...

Math - Can you see if my answers are correct? Directions find the GCF: (I did ...

math - 1.The base of a triangle is 5cm greater than the height. The area is 33cm...

Algebra - I need a step by step explanation of finding the GCF of (6ysquare -3y...

algebra - The first three equations I have solved, I would just appreciate ...

Algebra - The first three equations I have solved, I would just appreciate ...

math - 58. Let GCF (x,y) represent the greatest common factor of x any y. If p ...